Preclinical study of CD19 detection methods post tafasitamab treatment - Ilieva, Kristina; Eberl, Markus; Jaehrling, Jan; Blair, Derek; Patra-Kneuer, Maria; Boxhammer, Rainer; Alvarez Arias, Diana; Heitmüller, Christina (Frontiers in Immunology, 2023)
Introduction: Several CD19 targeted antibody-based therapeutics are currently available for patients with diffuse large B-cell lymphoma (DLBCL), including the Fc-modified antibody immunotherapy tafasitamab. This therapeutic landscape warrants the evaluation of potential sequencing approaches. Prior to a subsequent CD19-targeted therapy, CD19 expression on tafasitamab-treated patient biopsy samples may be assessed. However, no standardized methods for its detection are currently available. In this context, selecting a tafasitamab-competing CD19 detection antibody for immunohistochemistry (IHC) or flow cytometry (FC) may lead to misinterpreting epitope masking by tafasitamab as antigen loss or downregulation. Methods: We analyzed a comprehensive panel of commercially available CD19 detection antibody clones for IHC and FC using competition assays on tafasitamab pre-treated cell lines. To remove bound tafasitamab from the cell surface, an acidic dissociation protocol was used. Antibody affinities for CD19 were measured using Surface Plasmon Resonance (SPR) or Bio-Layer Interferometry (BLI). Results: While CD19 was successfully detected on tafasitamab pre-treated samples using all 7 tested antibody clones, all 8 tested FC antibody clones were confirmed to compete with tafasitamab. An acidic dissociation was demonstrated essential to circumvent CD19 masking by tafasitamab and avoid false negative FC results. Discussion: The current study highlights the importance of selecting appropriate CD19 detection tools and techniques for correct interpretation of CD19 expression. The findings presented herein can serve as a guideline to investigators and may help navigate treatment strategies in the clinical setting.